PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT ARJUNA CEMERLANG MOTORS CABANG TAMAN ANGGREK JAKARTA BARAT - Jihan Fitriadi, Rohmawan; Andriani, Jeni (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of Leadership and Work Motivation on employee performance at PT. Arjuna Cemerlang Motors, Taman Anggrek Branch, West Jakarta, either partially or simultaneously. The method used is quantitative. The sampling technique used saturated sampling and a sample of 60 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that leadership has a positive and significant effect on employee performance with the regression equation Y = 16.159 + 0.594X1, the correlation value obtained is 0.688, meaning that the two variables have a strong level of relationship. With a coefficient of determination value of 47.3% and hypothesis testing, t count > t table or (7.214 > 2.002). Thus, H0 is rejected and H1 is accepted, meaning that there is a significant influence of leadership on employee performance. Work motivation has a positive and significant effect on employee performance with the regression equation Y = 16.043 + 0.603X2, the correlation coefficient value is 0.649, meaning that the two variables have a strong level of relationship. The value of determination or contribution of influence is 42.1%. Hypothesis testing obtained a calculated t value > t table or (6.495 > 2.002). Thus, H0 is rejected and H2 is accepted, meaning that there is a significant influence of work motivation on employee performance. Leadership and work motivation simultaneously have a positive and significant effect on employee performance with the regression equation Y = 8.432 + 0.421X1 + 0.384X2. The correlation coefficient value or level of relationship between the independent variable and the dependent variable is 0.777, meaning it has a strong relationship. The value of the coefficient of determination or simultaneous contribution of influence is 60.3%. Hypothesis testing obtained a calculated F value > Ftable or (43.341 > 2.770). Thus H0 is rejected and H3 is accepted. This means that there is a significant simultaneous influence of leadership and work motivation on employee performance.